Regulating heights accuracy base position and covered runway aerodrome in regulatory documents - Y. Y. Stolbov; S. Y. Stolbova; R. V. Zotov; A. A. Poberezhnyy (Вестник СибАДИ, 2017)
The analysis of the accuracy of regulation height position of bases and covers runways at airports in their building regulations. Given the norms of precision altitude position Ba-ments and coatings for all types of runways of airfields: Off-tion of the actual elevation of the axis of each row of the design, the deviation of the transverse slope of each row of the design and significance of the algebraic difference (amplitude) elevations along the axis series, with a confidence level of P = 0,95 or P = 0,9. Noted disadvantages of valuation accuracy altitude position of bases and covers runways of airfields in the regulations. Proposed establishment of the technological processes at the device of their bases and covers not carry on limit, and in times standard deviation with a confidence level of P = 0,95 or P = 0,9.